2021
DOI: 10.1029/2021gl093936
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Clouds in Coral Bleaching Events Over the Great Barrier Reef

Abstract: The Great Barrier Reef (GBR) has experienced increasingly frequent coral bleaching events (CBEs) under present day global warming (Hughes et al., 2017;Stuart-Smith et al., 2018). Evidence for a dominant role of sustained elevated water temperature in the bleaching process, specifically thermal CBEs, is unequivocal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Analysis of the synoptic meteorology of GBR coral bleaching during El Niño events (1983–2016) between 23° 26′ 24″ °S to 14° 40′ 12″ °S found reduced high cloud cover was pivotal in inducing thermal stress and bleaching at individual coral reef scale and not background oceanic warming trends 18 . This finding was supported by a subsequent whole of GBR analysis of SST anomaly and cloud cover (1996–2018) which identified a strong relationship between total cloud cover and the one-month lagged SST during the summer coral bleaching season, confirming the relationship between cloud cover and coral bleaching 19 . This supports other research that found that the GBR, particularly the southern GBR, may be predisposed to coral thermal stress events because of less warm season cloud cover relative to French Polynesia and the central equatorial Pacific 16 .…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Analysis of the synoptic meteorology of GBR coral bleaching during El Niño events (1983–2016) between 23° 26′ 24″ °S to 14° 40′ 12″ °S found reduced high cloud cover was pivotal in inducing thermal stress and bleaching at individual coral reef scale and not background oceanic warming trends 18 . This finding was supported by a subsequent whole of GBR analysis of SST anomaly and cloud cover (1996–2018) which identified a strong relationship between total cloud cover and the one-month lagged SST during the summer coral bleaching season, confirming the relationship between cloud cover and coral bleaching 19 . This supports other research that found that the GBR, particularly the southern GBR, may be predisposed to coral thermal stress events because of less warm season cloud cover relative to French Polynesia and the central equatorial Pacific 16 .…”
Section: Introductionsupporting
confidence: 54%
“…The significance of reduced (enhanced) cloud cover in enhancing (suppressing) coral bleaching has been shown in previous research 16 , 17 , 19 , 25 . Cloud controls the amount of solar radiation received at the water surface and is the primary energy input to the surface energy balance of coral reefs.…”
Section: Discussionmentioning
confidence: 57%
“…Our main study domain is (as in Zhao et al, 2021) shown in Figure 1, which is defined as the Greater GBR region. Three subdomains are defined in Figure 1a, namely land, GBR, and open ocean.…”
Section: Investigation Area and Study Periodmentioning
confidence: 99%
“…By interacting with radiation, clouds modulate the flow of energy through the atmosphere across a range of temporal and spatial scales. The important role of local cloud cover in modulating the regional energy budget across the Great Barrier Reef (GBR) was explored in Zhao et al (2021), and the importance of clouds in preventing thermal coral bleaching was highlighted. Usually, warmer sea surface temperature (SST) is recognized as one of the main drivers of coral bleaching (Donner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation